Effect of Mn on the long-term cycling performance of AB5-type hydrogen storage alloy. (18th June 2021) - Chen, Xiangyu; Xu, Jie; Zhang, Weirong; Zhu, Shuai; Zhang, Na; Ke, Dandan; Liu, Jingjing; Yan, Kai; Cheng, Honghui
Abstract: Rare-earth AB5 -type hydrogen storage alloys are widely studied due to their extensive application potentials in hydrogen compressors, heat pump, Ni–MH batteries etc. However, their shortcomings such as plateau splitting and capacity degradation during hydrogen absorption/desorption hinder their practical applications. In this paper, we study the effect of Mn partial substitution for Ni on the plateau characteristics and long-term cycling performance of LaNi5- x Mn x alloys. It is found that Mn addition expands the lattice interstitial for hydrogen accommodation, thus prohibiting the plateau splitting phenomenon. In addition, the substitution of Mn for Ni stabilizes the crystal structure of the alloys against hydrogen absorption/desorption, thus relieving the capacity degradation. The capacity retention of the alloys at the 1000th cycle ( S 1000 ) increases from 83.2% ( x = 0) to 94.0% ( x = 0.75). But when x reaches 1, the hydrogen desorption reversibility is reduced due to the low plateau pressure, resulting in a slight decrease in capacity retention. Graphical abstract: Image 1 Highlights: Hydrogen storage properties of LaNi5- x Mn x alloys within 1000 cycles is studied. Degradation process is revealed from both property and structure points of view. Mn addition expands lattice interstitial and prohibits plateau splitting. Mn addition stabilizes crystal structure and relieves capacity degradation.